2021
DOI: 10.3390/microorganisms9020274
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Low Temperature and Ensiling Period on the Bacterial Community of Oat Silage by SMRT

Abstract: The objective of this study was to investigate how storage temperatures influence the bacterial community of oat silage during the ensiling process via PacBio single molecule, real-time sequencing technology (SMRT). Forage oat was ensiled at four different temperatures (5 °C, 10 °C, 15 °C, and 25 °C) and ensiling days (7, 14, 30, and 60 days). With the rise in storage temperature, the lactic acid content showed an increased trend. Acetic acid production was observed highest in silage fermented at 5 °C compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 31 publications
3
38
2
Order By: Relevance
“…The succession growth of LAB and their metabolic activities are essential for control the quality and safety of silage ( Driehuis et al, 2018 ). However, the fermentation of oat silage is a complex biochemical process that includes interactions between various microorganisms ( Duniere et al, 2017 ; Li et al, 2021 ). The activity of many microbes in silage may cause an extensive breakdown of amino acids into biogenic amines ( McDonald and Whittenbury, 1973 ; Scherer et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The succession growth of LAB and their metabolic activities are essential for control the quality and safety of silage ( Driehuis et al, 2018 ). However, the fermentation of oat silage is a complex biochemical process that includes interactions between various microorganisms ( Duniere et al, 2017 ; Li et al, 2021 ). The activity of many microbes in silage may cause an extensive breakdown of amino acids into biogenic amines ( McDonald and Whittenbury, 1973 ; Scherer et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ensiling at high temperatures reduces both the lactic acid (LA) concentration and aerobic stability ( Ashbell et al, 2002 ). Moreover, it has been reported that temperature affects the bacterial diversity and fermentation quality of silage ( Wang et al, 2019 ; Li et al, 2021 ). Epiphytic bacterial communities in fresh forage depends mainly on geographical location, climate, and cutting ( Guo et al, 2018 ; Yang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mold and yeast were not detected in all samples, which could be due to low pH values. As Li et al [33] reported, anaerobic conditions and organic acid can inhibit yeast growth, especially after long storage periods. Additionally, ammonia-N contents decreased in both LM and WLM, which typically occurs during the ensiling process and is a result of the fermentation of Clostridium or the activity of plant protease [34].…”
Section: Discussionmentioning
confidence: 98%